PENGEMBANGAN SOAL UJIAN BERBASIS TEKNOLOGI INFORMASI MENGGUNAKAN WONDERSHARE QUIZ CREATOR - Erna Kumalasari Nurnawati; Muhammad Sholeh; Edhy Sutanta (DHARMA BAKTI, 2019)
The use of information technology has penetrated all fields, including the education sector. Included in the delivery of learning materials and managing exam questions is also inseparable from this phenomenon. Teachers as the main function of formal education to the younger generation must be able to follow this development so that the teaching and evaluation process for students can run more optimally. The use of software in making teaching materials and learning evaluation (exam questions) can improve teacher performance and quality in providing services to students. The Community Service activity aims to provide information technology-based test questions training using the Wondershare Quiz Creator software, where in addition to the teachers being able to make nine types of questions easily, the documentation and implementation of the test can be arranged according to the needs and desires of the test questions. Documentation and updating of questions can be done easily and saves savings media because test questions are stored in softcopy both in document form and in application form. The teacher can also conduct online evaluations and randomization of questions can be done automatically so as to minimize cheating in the exam. This activity was carried out at SMK Negeri 1 Tembarak with participants from the study programs of Network, Electronics and Mechanical Engineering Management.